Cahm, The Dreyfus Affair In The French Society And Politics - Kriegel, Abraham (Teaching History: A Journal of Methods, 1997)
The year 1994 marked a century since the inception of the Dreyfus Affair, the sensational case that transfixed France and the Western world for a dozen years. The facts of the case are no longer in dispute. Alfred Dreyfus, a Jew and a captain in the French army, was falsely accused of spying for Germany, convicted by a military court, publicly degraded, and sentenced to life imprisonment on Devil's Island. The general staff, all too willing to convict Dreyfus, ignored the paucity of evidence and adamantly insisted on his guilt, even when the real culprit, the unscrupulous Major Esterhazy, was exposed. The case became a cause célèbre, with enduring political consequences.